Fabrication of High-Density Multimodal Neural Probes Based on Heterogeneously Integrated CMOS - Mun, Ju Hee; Kim, Miji; Shin, Wooyeon; Park, Yongjun; Kim, Kanghwan; Cho, Il-joo; Shim, Jae Won; Kim, Min Soo; Lee, Sunwoo; Kim, Jeongjin; Lee, Changhyuk (Wiley-VCH Verlag, 2026)
Neural interfaces that simultaneously capture electrical activity and cell-type-specific dynamics across molecularly defined populations are essential for understanding brain function. Monitoring these neural activities could help understand the complex mechanisms and disorders of the brain. While micro-electro-mechanical systems (MEMS) based neural probes provide multi-sensor integration, their lack of on-chip signal processing limits the channel density. On the other hand, complementary metal-oxide-semiconductor (CMOS) probes offer on-chip amplification and multiplexing to enable high channel density, yet the high foundry tape-out cost hinders their broader adoption. Here, we achieve a near two orders of magnitude reduction in per-wafer cost by applying simplified post-CMOS processing on a multi-project wafer (MPW) while advancing the probe functionality. This approach requires only two photolithography and three etching steps for CMOS post-processing through the decoupled sensor customization, while the front-end circuits are defined by CMOS, multimodal sensors (electrodes and photodiodes) are defined through post-processing. Our 13-shank probe integrates 416 electrodes and 832 photodiodes, and complete on-chip signal processing, enabling simultaneous high-density electrical and optical recording. We validated the operational feasibility of the proposed system under both in vitro and in vivo conditions. Based on these results, we propose the first fully integrated active multimodal neural probe architecture for high-density electrical and optical interfacing.